2012
DOI: 10.7783/kjmcs.2012.20.6.487
|View full text |Cite
|
Sign up to set email alerts
|

Thrips in Medicinal Crops in Korea:Identification and Their Damages

Abstract: : Damages of medicinal crops by thrips and identification of thrips species were investigated by periodic surveys on major medicinal crops, Platycodon grandiflorum, Schizandra chinensis, Codonopsis lanceolata, Lycium chinense, Bupleurum falcatum, Ledebouriella seseloides, Angelica gigas, Glycyrrhiza uralensis, Liriope platyphylla, Atractyloides sp., once or twice a month in Suwon, Eumseong, Jecheon, Pyeongchang, Chyungyang from May to October in 2012. Thrips and their damages were found at all of the medicinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…On the other hand, the results are in agreement with those of previous studies such as Bueno et al,(8), Kahramanoğlu and Umar(17), Kang et al, (18), and Mehta et al, (24) who reported that the cuttings should be collected earlier so as to be succeeded.…”
Section: Shoot Length (Cm)supporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the results are in agreement with those of previous studies such as Bueno et al,(8), Kahramanoğlu and Umar(17), Kang et al, (18), and Mehta et al, (24) who reported that the cuttings should be collected earlier so as to be succeeded.…”
Section: Shoot Length (Cm)supporting
confidence: 92%
“…These results might be attributed to the differences in carbohydrate contents of the cutting tissues which act as the main sources of energy needed for root formation (4). Many researchers emphasize the difference in the rooting capacity of cuttings taken at different times (10, 16,18), this could be related to the difference in the hormonal balance that favors the rooting of hardwood cuttings taken at different times (8).…”
Section: Rooting%mentioning
confidence: 99%
“…Ribosomal RNA-ITS markers have been used for detection of S. dorsalis , T. palmi , F. tritici (Fitch), F. intonsa (Trybom), F. cephalica (Crawford), H. cahirensis (Trybom), Dendrothrips eremicola Priesner, Kakothrips pisivorus (Westwood), Hydatothrips kassimianus (Priesener), and Ceratothripoides claratris (Shumsher) [ 46 , 114 , 115 , 116 , 117 , 118 ]. ITS has been used as a natural choice of nuclear marker to substantiate mitochondrial marker-based identification and allow multi-locus phylogenetic analyses of F. occidentalis , F. intonsa , F. fusca (Hinds), T. tabaci , and Megalurothrips distalis (Karny) [ 72 , 119 , 120 ]. ITS sequences are also useful in distinguishing cryptic species of F. schultzei [ 97 ], S. dorsalis [ 121 , 122 ], T. tabaci [ 123 , 124 ], and S. aurantii [ 110 ].…”
Section: Pcr-based Identification Of Thrips Using Molecular Markersmentioning
confidence: 99%
“…장 발생 해충조사 (Kim, 1994), 경남지역 5 종 약용작물에 대한 해충조사 (Shin et al, 2002), 약용작물 전시포 발생 곤 충상 조사 (Lee et al, 2007) 및 약용작물 발생 총채벌레류 종류 및 피해조사 (Kang et al, 2012) (Yudin et al, 1986;Ananthakrishan, 1993 (Bailey, 1948;Köppä, 1970;Nakahara, 1995;Mound and Kibby, 1998) 높은 생식능력으로 빠르게 개체군을 형성하여 작물에 심각한 피해를 준다 (Jiang et al, 2015(Jiang et al, , 2016 (Kamm, 1971;Mound and Masumoto, 2009). 특 히 피해 받은 티모시는 품질이 크게 감소하며, 종자로부터 출 아한 옥수수 떡잎이 피해를 받게 되면 수량이 크게 감소된다 (Reisig et al, 2009).…”
unclassified